2023
DOI: 10.3390/biomedicines11010122
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effects of Non-Thermal Plasma in a Model for Latent HIV-1 Infection: Implications for an HIV-1-Specific Immunotherapy

Abstract: In people living with HIV-1 (PLWH), antiretroviral therapy (ART) eventually becomes necessary to suppress the emergence of human immunodeficiency virus type 1 (HIV-1) replication from latent reservoirs because HIV-1-specific immune responses in PLWH are suboptimal. Immunotherapies that enhance anti-HIV-1 immune responses for better control of virus reemergence from latent reservoirs are postulated to offer ART-free control of HIV-1. Toward the goal of developing an HIV-1-specific immunotherapy based on non-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
0
0
Order By: Relevance
“…The study demonstrated that pre-treating MDM with plasma decreased viral reverse transcriptase activity by more than two-thirds, and inhibited the other steps necessary for a successful virus infection (i.e., by preventing virus-cell fusion, inhibiting viral reverse transcription, and impeding viral integration), without having any cytotoxic effects on the macrophages. The possible immunomodulatory mechanisms of plasma that may be used to induce antiretroviral therapy-free control of HIV-1 recrudescent infection have been reported for the first time by Mohamed et al [148]. The fact that plasma can be employed to improve latently infected cells' capacity to trigger an immunological response to HIV-1 serves as the foundation for the authors' suggested immuno- Furthermore, treatment using plasma has been employed to combat three significant animal pathogens: avian influenza virus (AIV), Newcastle disease virus (NDV), and porcine reproductive and respiratory syndrome virus (PRRSv).…”
Section: Virusesmentioning
confidence: 98%
“…The study demonstrated that pre-treating MDM with plasma decreased viral reverse transcriptase activity by more than two-thirds, and inhibited the other steps necessary for a successful virus infection (i.e., by preventing virus-cell fusion, inhibiting viral reverse transcription, and impeding viral integration), without having any cytotoxic effects on the macrophages. The possible immunomodulatory mechanisms of plasma that may be used to induce antiretroviral therapy-free control of HIV-1 recrudescent infection have been reported for the first time by Mohamed et al [148]. The fact that plasma can be employed to improve latently infected cells' capacity to trigger an immunological response to HIV-1 serves as the foundation for the authors' suggested immuno- Furthermore, treatment using plasma has been employed to combat three significant animal pathogens: avian influenza virus (AIV), Newcastle disease virus (NDV), and porcine reproductive and respiratory syndrome virus (PRRSv).…”
Section: Virusesmentioning
confidence: 98%